The Routledge companion to literary media - Ensslin, Astrid; Round, Julia; Thomas, Bronwen (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Routledge Companion to Literary Media examines the fast-moving present and future of a media ecosystem in which the literary continues to play a vital role. The term 'literary media' challenges the tendency to hold the two terms distinct and broadens accepted usage of the literary to include popular cultural forms, emerging technologies and taste cultures, genres, and platforms, as well as traditions and audiences all too often excluded from literary histories and canons. Featuring contributions from leading international scholars and practitioners, the Companion provides a comprehensive guide to existing terms and theories that address the alignment of literature and a variety of media forms. It situates the concept in relation to existing theories and histographies; considers emerging genres and forms such as locative narratives and autofiction; and expands discussion beyond the boundaries by which literary authorship is conventionally defined. Contributors also examine specific production and publishing contexts to provide in-depth analysis of the promotion of literary media materials. The volume further considers reading and other aspects of situated audience engagement, such as Indigenous and oral storytelling, prize and review cultures, book clubs, children, and young adults. This authoritative collection is an invaluable resource for scholars and students working at the intersection of literary and media studies"--
Keywords: Mass media and literature; Hypertext literature -- History and criticism; Literature and technology; Intermediality; Literature, Modern -- 21st century -- Philosophy; LITERARY CRITICISM / General; LITERARY CRITICISM / Books & Reading